COVID-19’S FACING POLICIES AS PUBLIC CALAMITY AND THE RESPECTIVE LEGAL RESPONSIBILITIES OF THE PUBLIC AGENT - Leal, Rogério Gesta (Revista do Direito, 2022)
In these pandemic times caused by the Covid-19 virus, many government actions by the Federal Union, States and Municipalities, which demand urgency and are costly, are and will need to be developed overcoming certain formal requirements of traditional procedures, which presents risks of abuse of authority and deviations of power. In view of this, we intend in the present text to evaluate some risks and dangers of these scenarios, posing as a problem to be faced if it is possible and necessary to have preventive and curative controls, in real time, of the management of this public calamity that configures Covid-19, having as a neural hypothesis that it is possible to combine emergency measures in states of emergency and public calamity with systems of internal and external controls of the instituted powers. As specific objectives, we will try to conceptually demarcate some of the constitutive elements of the social and administrative disorder that characterize the Risk Society that we live in, especially those brought about by the referred pandemic, identifying the importance of establishing limits of restraint to its causes and consequences; finally, we want to maintain that disregarding the Brazilian legal system in these situations, deserves effective control, avoidance and reprimand through normative mechanisms that we already have.